Prognostic Implications of Ambulatory N-Terminal Pro-B-Type Natriuretic Peptide Changes in Patients with Continuous-Flow Left Ventricular Assist Devices. Issue 4 (3rd August 2021) - Ali, Abbas; Akintoye, Emmanuel; Ruiz Duque, Ernesto; Kshetri, Rupesh; Shetty, Suchith; Sharma, Umesh C.; Johnson, Carol M.; Panos, Anthony L.; Briasoulis, Alexandros; Alvarez, Paulino
Abstract : Data regarding the role of N-terminal Pro-B-type natriuretic peptide (NT-pro BNP) in patients with a continuous-flow left ventricular assist device (CFLVAD) is scarce. To evaluate the prognostic implications of measuring both absolute values and changes in NT-pro BNP concentrations in ambulatory patients with a CFLVAD, we performed a retrospective study of 168 consecutive patients who had an LVAD implantation at our institution and survived beyond their index hospitalization. Of these, 127 patients (56.2 ± 12.5 years, 21.2% female) had NT-pro BNP measured at 1 and 3 months postdischarge in ambulatory settings. Compared to the NT-pro BNP concentration at 1 month, 94 patients (74%) had a decline, and 33 patients (26%) had an increase in concentrations, from their 1 month baseline. After a median follow-up of 17 months, a total of 53 (41.7%) adverse events occurred. Of these, 37 (69.8%) were heart failure (HF) hospitalizations, and 16 (30.2%) were deaths. For each 1, 000 unit increase in NT-pro BNP concentration at 3 months, there was a 17% increase in the risk of HF hospitalization or death (hazard ratio [HR] = 1.17, 95% confidence interval [CI] = 1.04–1.32, p = 0.007). Conversely, each 1000 unit decline during the same time, was associated with an 11% decrease in the risk of HF hospitalization or death (HR = 0.89, 95% CI = 0.77–0.98, p = 0.04). In conclusion, in patients with a CFLAD, an increase in NT-pro BNP concentration from 1 to 3 months is associated with an increased risk of HF hospitalization and death. In contrast, a decline is associated with a reduction in the risk of HF hospitalization and death.